Antidiabetic Activity of Noni (Morinda citrifolia) Extract on Swiss Webster Male Glucagon-Induced Mice - Jessica Rusli (UIN Syarif Hidayatullah Jakarta, 2022)
The antidiabetic activity of noni (Morinda citrifolia) extract on the blood glucose level of Swiss Webster male mice (Mus musculus) has been examined. This research aims to study the antidiabetic activity of noni fruit extract on blood glucose level by either induced or not induced with glucagon. Twenty-eight Webster male mice were divided into two main treatment groups. The first treatment group was further divided into four treatment sub-groups. These are (i) blank control (without any treatment), (ii) given distilled water only, (iii) given the extract in a dosage of 1,5 g/kg body weight (bw), and (iv) given the extract in a dosage of 3 g/kg bw. The second treated group was divided into three other treatment group. These are: (i) glucagon+ distilled water, (ii) glucagon+the extract in a dosage of 1,5 g/kg bw, and (iii) glucagon+the extract in a dosage of 3 g/kg bw. The experiment was done with four replicates to each sub-group. The volume of distilled water and the extract were given by gavage in a dosage of 10 ml/kg bw, whereas the glucagon was given through intramuscular injection in a dosage of 20 µg/kg bw. The treated sub-groups without glucagon were injected with distilled water and the extract once every two weeks for eight weeks (1th,3th,5th,7th week) with per week interval for blood sampling (zero,2nd,4th,6th,8th week). The blood glucose levels (BGL) of this sub-group is fasting blood glucose level (BGLf) and two hours post-prandial (2-hrs pp) blood glucose level). The sub-groups with glucagon injection were given distilled water and the extract once a week for four weeks (1th-4th week) with three times per week blood sampling, namely before glucagon injection (BGLa), 10 minutes after the injection (BGLb) and 2 minutes after distilled water or the extract. The results of the statistic test showed (ANOVA p<0,05) that BGL of noni fruit extract-treated mice (doses: 1,5 and 3 g/kg bw) without glucagon injection for eight weeks, tends to decrease. The distilled water feeding does not affect BGL. It can be seen that during 8 weeks of distilled water treatment, it appears that BGLf and BGLe of the distilled water group were not significantly different from the control group. Mice treated with noni fruit extract (doses: 1,5 and 3 g/kg bw) and glucagon injection for four weeks, showed constant BGL. The conclusion is that nony fruit extract helps to decrease blood glucose levels in both groups of mice either induced or not induced with glucagon. That can be seen from the result of statistical tests that shows BGLf and BGLe of the noni group, both at a dose of 1.5 g / kg bw and 3 g / kg bw, from week 2 to week 8 were significantly different from the control group. Meanwhile, in the mice treated with glucagon in the noni group with both doses, BGL decreased after administration of noni. That also shows the significant difference of BGLf and BGLe of the noni group with the control group